Effects of egg exposure to atrazine and/or glyphosate on bone development in Podocnemis unifilis (Testudines, Podocnemididae) - Hirano, Líria Queiroz Luz; Alves, Letícia da Silva; Menezes-Reis, Lorena Tannús; Mendonça, Juliana dos Santos [UNESP]; Simões, Karina; Santos, André Luiz Quagliatto; Vieira, Lucélia Gonçalves (Elsevier, 2019)
This study was designed to investigate skeletal changes in Podocnemis unifilis embryos derived from artificially incubated eggs exposed to different concentrations of atrazine, glyphosate or atrazine and glyphosate mixture. Forty-two eggs were randomly allocated to one of seven trays containing vermiculite treated distilled water (control group) or the following solutions: 2 or 200 μg L-1 of atrazine (groups A1 and A2 respectively); 65 or 6500 μg L-1 of glyphosate (groups G1 and G2 respectively); 2 μg L-1 and 65 μg L-1 or 200 μg L-1 and 6500 μg L-1 of atrazine and glyphosate mixture (groups AG1 and AG2 respectively). Three eggs per tray were randomly collected on days 30 and 50 of the incubation period. Embryos were submitted to soft tissue diaphanization and stained with Alizarin red S or Alcian blue for morphological analysis of bone and cartilage tissues; histological analysis was performed to confirm ossification changes. Findings were compared between groups. Morphological changes were limited to sclerotic ring features and number of ribs. Malformations rates differed significantly (p < 0.05) between embryos in the control and treated groups A2, AG1 and AG2. Concurrent exposure to atrazine and glyphosate did not affect the presence or severity of embryonic malformations and was not associated with appendicular skeleton changes in P. unifilis embryos. However, further studies focusing on the axial skeleton with particular emphasis on rib abnormalities are warranted.
Keywords: Ecotoxicology; Osteogenesis; Pesticides; Skeleton; Yellow‐spotted river turtles